Relasi Agama, Kebudayaan dan Politik pada Masyarakat Batak Toba di Kabupaten Samosir: The Relationship between Religion, Culture, and Politics in the Batak Toba Community in Samosir Regency - Harisan Boni Firmando; Elvri Teresia Simbolon; Roida Lumbantobing (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
Religion, culture, and politics form a unified entity in society that cannot be separated. These three elements shape human life both socially and as citizens. The purpose of this study was to explore the relationship between religion, culture, and politics within the Toba Batak community in Samosir Regency. This research utilized qualitative methods to comprehensively understand the experiences of the subjects. The findings reveal that the relationship between religion, culture, and politics is evident in the implementation of the 'dalihan na tolu' kinship system. The Toba Batak community exhibits openness towards others outside their tribe, a practice facilitated by incorporating clan affiliations as a basis for determining kinship. The culture of solidarity in the Batak Toba community influences their political behavior. The community supports their family members who run in general elections, with this solidarity serving as both social and economic capital for the Toba Batak people engaging in political activities, particularly for those aspiring to become regional head candidates or council members. In selecting leaders, the Batak Toba community considers not only the educational and other qualifications of potential leaders but also their sociological background. AbstrakAgama, kebudayaan, dan politik merupakan satu kesatuan di dalam masyarakat yang tidak dapat dipisahkan. Ketiga hal tersebut menyebabkan kehidupan manusia sebagai makhluk sosial dan sebagai warga negara berlangsung. Kajian ini bertujuan untuk mengetahui relasi agama, kebudayaan dan politik pada masyarakat Batak Toba di Kabupaten Samosir. Kajian ini menggunakan metode kualitatif untuk memahami. Hasil Kajian ini menunjukkan relasi agama, kebudayaan dan politik terlihat dalam implementasi sistem kekerabatan dalihan na tolu. Masyarakat Batak Toba dengan orang lain di luar suku Batak Toba, keterbukaan tersebut dilakukan dengan penabalan marga sebagai dasar suku Batak Toba untuk menentukan sistem kekerabatan. Budaya solidaritas menjadi pedoman masyarakat Batak Toba dalam berperilaku politik. Masyarakat akan membantu keluarganya yang maju dalam pemilihan umum. Solidaritas ini merupakan modal sosial sekaligus modal ekonomi bagi masyarakat Batak Toba yang melakukan aktivitas politik, khususnya anggota masyarakat yang maju menjadi calon kepala daerah dan anggota dewan. Pemilihan pemimpin pada masyarakat Batak Toba hingga kini masih memperhitungkan latar belakang calon seorang pemimpin. Latar belakang bukan hanya dari pendidikan atau modal lain dari calon pemimpin yang mumpuni, namun lebih kepada aspek-aspek sosiologis.